PSYCHOMETRIC CHARACTERISTICS OF THE QUESTIONNAIRE ON POSITIVE AND NEGATIVE AFFECTS (OPANA), BASED ON THE PANAS SCALES - Klimanska, Maryna; Haletska, Inna (PSYCHOLOGICAL JOURNAL, 2020)
The article aim is to describe the development and testing of the psychometric characteristics of OPANA (the Questionnaire on Positive and Negative Affects), based on the PANAS scales (Watson, Clark, and Tellegen, 1988). The sample of 777 participants was involved in the development and approbation of the questionnaire (age 17-72, 300 men, 477 women). The differences between the survey’s results of men and women, as well as differences depending on the methods of data collection (paper-and-pencil or online) were presented. The high internal reliability of the questionnaire scales (Cronbach alpha for the “during the past few weeks” instruction was 0.89 for positive affect (PA) and 0.88 for negative affect (NA) was confirmed. The test-retest reliability (N = 103 participants) was r = 0.7 for PA and r = 0.48 for NA. The exploratory factor analysis was used to analyze the factor structure of the questionnaire: as a result, a three-factor structure of the questionnaire was determined. The confirmatory factor analysis confirmed the equivalence of the two-factor and three-factor models (the three-factor model fit indices were χ² / df = 2.94; RMSEA = 0.059; CFI = 0.94; TLI = 0.93; the two-factor model fit indices were χ² / df = 2.89; RMSEA = 0.058; CFI = 0.942; TLI = 0.93). Significant correlations of PA and NA scales with the scales of affect balance, satisfaction with life, dispositional optimism, psychological hardiness, as well as extraversion, openness to experience and emotional stability proved the construct validity of the questionnaire. OPANA can be used as a reliable and valid psychodiagnostic tool. The proposed list of descriptors makes it possible to distinguish between positive and negative affects, to analyze them according to the temporal context of an evaluation, to conduct longitudinal studies and to track the dynamics of changes. Because the research was conducted with a large group of participants, most of whom were students and representatives of different social groups, the obtained results can be only a starting point for exploring the possibilities of applying the Questionnaire in Ukrainian psychological science. The method should be probated with groups of different ages and with specific groups, for example, alcohol and drug addicts, people with deviant or delinquent behaviour, in order to clarify the normative data for the questionnaire.